Spine and Whiplash Injuries Related to Passenger Car Crashes in Malaysia - Zulkipli, Z.H.; Mohd Faudzi, S.A. (Journal of the Society of Automotive Engineers Malaysia, 2020)
Spinal injury is one of the most devastating traumas that can be sustained in a motor vehicle crash. In passenger car crashes, the most common injuries related to the spine is whiplash injury or Whiplash Associated Disorder (WAD); however, the injury was relatively unknown in Malaysia. This study explored the possibility of elucidating whiplash injury locally by studying the insurance claims made by passenger car occupants involved in traffic crashes. The objectives of the study were to investigate the prevalence and to identify the injury pattern of the spine and whiplash injury. The data were collected retrospectively from closed files of the Third-Party Bodily Injury (TPBI) insurance claims database for the year 2013-2015. Each occupants’ injuries were extracted from the medical report and were classified according to the Abbreviated Injury Scale (AIS). A total of 500 cases of passenger car crashes were obtained from the insurance database and out of the total occupants involved, 866 injured occupants were included in the analysis. The results demonstrated that spine injuries have very low occurrence in Malaysia relative to other injury types, and whiplash-specific injuries are even rarer among passenger car crash victims in Malaysia. The most common vertebra level to be affected was the cervical spine, especially the C5-C6 vertebra, and this can be seen mostly for the drivers and front passengers. The low occurrence of spine injury is comparable to other countries, but the rare whiplash injury may indicate the ‘whiplash culture’ is not prevalent in Malaysia.